Research Note: It's not just stress—fecal contamination of plumage may affect feather corticosterone concentration - T. Bartels (Elsevier, 2021)
ABSTRACT: The feather corticosterone concentration (fCORT) is increasingly used to assess long-term stress in birds as this indicator provides the potential to retrospectively evaluate the adrenocortical activity of a bird during the growth period of a feather over several weeks in one sample. However, there is still a lack of knowledge concerning external factors which can potentially influence fCORT in birds. The aim of the present study was to determine whether fCORT in laying hens is affected by previous fecal contamination of the plumage. Fully grown primaries 5 (P5s) of laying hens (n = 40) were used for the study. To test the effects of fecal contamination on fCORT, freshly defecated droppings from laying hens were collected and mixed manually. In order to simulate practical and at the same time standardized contamination, the upper surface of the previously determined middle third of the right P5 of each hen then was evenly coated with the paste prepared from fresh feces. The treated feathers were stored for 24 h protected from light at room temperature under a film cover to prevent evaporation. Thereafter, the applied layer of excreta was removed manually. Contralateral P5s of the same individuals were stored under identical conditions and served as controls. Both treatment and control feathers were washed in an aqueous soap solution, rinsed several times in pure water and air-dried subsequently. After pulverization and methanolic extraction, fCORT was analyzed by ELISA. The mean fCORT of treatment P5s (reference ‘feather length’: 12.88 ± 3.16 pg/mm; reference ‘feather weight’: 7.81 pg/mg ± 1.86 pg/mg) were significantly higher (P < 0.001) than those of control P5s (reference ‘feather length’: 9.76 ± 2.42 pg/mm; reference ‘feather weight’: 5.93 ± 1.44 pg/mg). Our results show that previous contamination with excreta can increase fCORT, which was detectable even after a washing procedure prior to analysis. In conclusion, fecal contamination of feathers is a significant influencing factor that has to be considered when applying fCORT measurements.